2017
DOI: 10.4300/jgme-d-16-00212.1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of “See the City You Serve” Field Trip: An Educational Tool for Teaching Social Determinants of Health

Abstract: Background There has been limited evaluation of tools for teaching social determinants of health (SDOH).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 3 publications
0
12
1
Order By: Relevance
“…For instance, some have established medical and/or veterinary community clinics [ 20 , 28 ] where students work alongside trained professionals to provide clinical care to underserved communities. Further, one university implemented a community-guided bus trip through local neighborhoods to teach medical interns about challenges affecting their patients [ 29 ]. Similar to this, our veterinary medical students participate in community service programs in collaboration with an animal welfare organization during Years 2–4 of the DVM degree.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, some have established medical and/or veterinary community clinics [ 20 , 28 ] where students work alongside trained professionals to provide clinical care to underserved communities. Further, one university implemented a community-guided bus trip through local neighborhoods to teach medical interns about challenges affecting their patients [ 29 ]. Similar to this, our veterinary medical students participate in community service programs in collaboration with an animal welfare organization during Years 2–4 of the DVM degree.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to this, our veterinary medical students participate in community service programs in collaboration with an animal welfare organization during Years 2–4 of the DVM degree. Insights learned through evaluation of these initiatives confirm that these experiences greatly expand student understanding of the social determinants of human health [ 29 ] as well as the connection between human and animal welfare (One Welfare) [ 28 ]. Nevertheless, these experiences do not extend to consideration of the ecological factors that contribute to health and wellbeing outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Our literature review revealed no validated questionnaires measuring medical trainees' knowledge or practice related to the SDOH. Therefore, we developed a questionnaire for this study by adapting items from previously published instruments assessing related areas [10][11][12][13][14]. We followed Moore's taxonomy of outcomes as a framework to develop questions assessing residents' selfreported competence identifying and addressing SDOH [15].…”
Section: Measurementsmentioning
confidence: 99%
“…A field trip is a journey that allows students and teachers to leave the classroom to experience settings away from their normal environment [7]. Field trips are sometimes conducted in medical programmes as a direct approach to teaching and learning essential knowledge and activities in medical practice [8][9][10][11]. The studied field trip programme is held in Summer Semester to allow students to recognize and directly in contact with the raw Chinese herbs in the wild that they have previously studied in the "Chinese Materia Medica" course.…”
Section: Prior Workmentioning
confidence: 99%